2007
DOI: 10.1186/1472-6963-7-30
|View full text |Cite
|
Sign up to set email alerts
|

The links between health-related behaviors and life satisfaction in elderly individuals who prefer institutional living

Abstract: Background: Life satisfaction among residents of institutions is becoming an important issue in a rapidly aging population. The aim of this cross-sectional study was to investigate the links between life satisfaction and health-related behaviors amongst functionally independent elderly people who prefer institutional living in İstanbul, Turkey. Methods:The socio-demographic characteristics, health-related behaviors, leisure-time activities and fall histories of 133 residents of an institution in Istanbul were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 35 publications
3
20
0
Order By: Relevance
“…Financial problems may lead to restrictions in a person's ability to live an independent life and to fulfill the needs or wishes to socialize. Economic status as a predictor of life satisfaction has previously been emphasized by Inal et al [7] and Lipovcan et al [8]. These findings are consistent with ours in that the empty-nest elderly had lower income compared to the not-empty-nest ones; therefore, their low income was a predictor of low life satisfaction.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Financial problems may lead to restrictions in a person's ability to live an independent life and to fulfill the needs or wishes to socialize. Economic status as a predictor of life satisfaction has previously been emphasized by Inal et al [7] and Lipovcan et al [8]. These findings are consistent with ours in that the empty-nest elderly had lower income compared to the not-empty-nest ones; therefore, their low income was a predictor of low life satisfaction.…”
Section: Discussionsupporting
confidence: 95%
“…Elderly people with low income had a significantly lower life satisfaction than those with moderate/high income [7]. People with higher income felt happier and more satisfied with their life as a whole [8].…”
Section: Introductionmentioning
confidence: 99%
“…In line with this tenet, research has shown that the more that older adults engage in social, physical and cognitive activities, the happier they are (Inal et al . ). The health benefits of physical activity for older adults are well documented in terms of reduced mortality (Chakravarty et al .…”
Section: Introductionmentioning
confidence: 97%
“…People living with limitations to physical activity might have fewer opportunities to be satisfied with life or experience happiness, which can have a negative effect on their overall quality of life (QOL) (Newall et al 2013). In line with this tenet, research has shown that the more that older adults engage in social, physical and cognitive activities, the happier they are (Inal et al 2007). The health benefits of physical activity for older adults are well documented in terms of reduced mortality (Chakravarty et al 2008), better functional, physical and more positive affect (Netz et al 2007), and less cognitive decline (Klusmann et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Access to medical services has been consistently related to life satisfaction among older adults in China (Zhang & Liu, 2007). In addition, some studies indicated that regular activities including physical and leisure activities are significantly related to life satisfaction among older adults, whereas not participating in activities is associated with life dissatisfaction (Helvik, Engedal, Krokstad, & Selbaek, 2011;Inal, Subasi, Ay, & Hayran, 2007).…”
Section: Introductionmentioning
confidence: 99%